2021
DOI: 10.1155/2021/5544063
|View full text |Cite
|
Sign up to set email alerts
|

Synchronization of Complex Dynamical Networks on Time Scales via Pinning Control

Abstract: In this paper, we are concerned with the synchronization problem of complex dynamical networks on time scales. Some pinning synchronization criteria, which combine main characteristics of time scales with main parameters of the pinning controlled network, are established. A numerical example is also included to verify the effectiveness of the results obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…In [24], through the pinning part of the network nodes with simple aperiodic intermittent controllers, the addressed dynamical networks can achieve global quasi-synchronization. In [25], the pinning synchronization strategy, which combines main characteristics of time scales and main parameters of the pinningcontrolled network, is established. In [26] and [27], the pinning control is introduced into the MGs.…”
Section: Introductionmentioning
confidence: 99%
“…In [24], through the pinning part of the network nodes with simple aperiodic intermittent controllers, the addressed dynamical networks can achieve global quasi-synchronization. In [25], the pinning synchronization strategy, which combines main characteristics of time scales and main parameters of the pinningcontrolled network, is established. In [26] and [27], the pinning control is introduced into the MGs.…”
Section: Introductionmentioning
confidence: 99%
“…Among all kinds of networks, biological neural network is a persistent and hot topic. In the past decade, a lot of studies have been devoted to the synchronization of all kinds of neural networks under different conditions (Li et al 2003 ; Cao and Lu 2006 ; Yu et al 2009 ; Ehrich et al 2013 ; Fan et al 2018 ; Kong and Sun 2021 ; Wouapi et al 2020 ) because of studies have shown that Parkinson’s, epilepsy and other brain deficits are caused by the damage to the ability of neurons to synchronize with their neighbors. As shown in Njitacke et al ( 2021 ), the synchronization of neurons under different structures and parameters were conducted according to the state estimation error system and the control strategy.…”
Section: Introductionmentioning
confidence: 99%